Post-training activation of Rac1 in the basolateral amygdala is required for the formation of both short-term and long-term auditory fear memory - Gao, Qinqin; Yao, Wenqing; Wang, Junjun; Yang, Tong; Liu, Cao; Tao, Yezheng; Chen, Yuejun; Liu, Xing; Ma, Lan (Frontiers in Molecular Neuroscience, 2015)
Rac1, a member of the Rho family of small GTPases, is crucial for morphological changes of the mature neuronal synapse including spine formation and activity-dependent spine enlargement, while its role in the formation of associated memories, such as conditioned fear memory, is not clear. Here we report that selective deletion of Rac1 in excitatory neurons, but not in parvalbumin inhibitory neurons, impaired short- and long-term memories (STM and LTM) of fear conditioning. Conditional knockout of Rac1 before associative fear training in the basolateral amygdala (BLA), a key area for fear memory acquisition and storage, impaired fear memory. The expression of dominant-negative mutant of Rac1, or infusion of Rac1 inhibitor NSC23766 into BLA blocked both STM and LTM of fear conditioning. Furthermore, selective inhibition of Rac1 activation in BLA immediately following fear conditioning impaired STM, demonstrating that fear conditioning-induced Rac1 activation in BLA plays a critical role in the formation of both STM and LTM of conditioned fear.